Determining the acoustic field distribution of ultrasonic multi-element probes - Opieliński, Krzysztof; Gudra, Tadeusz (Archives of Acoustics, 2006)
The paper presents a universal method of determining the distribution of acoustic fieldof multi-element probes designed for applications in ultrasound transmission tomography(UTT). This method allows us to calculate the acoustic field for different sectors of the probewith assigned geometry of elementary transducers’ location. The idea is to sum acoustic fieldsgenerated by all elementary transducers with the use of geometrical transformations of coordinatesof location of the discussed points of the acoustic field against each of the transducers.In order to verify the calculation results measurements of acoustic field distribution were alsocarried out for selected sectors of these probes. On the basis of an analysis of calculationresults the size of electronically switched transmitting sector was optimized (in the sense ofthe number of concurrently radiating elementary transducers) for a linear and a ring ultrasonicmulti-element probes from the point of view of their use for visualizing the inside of abiological structure by means of UTT.